FREQUENCY OF COMMON BARRIER IN ADOPTING FAMILY PLANNING METHODS BY RURAL MARRIED WOMEN PRESENTING FOR ANTENATAL CARE IN A TERTIARY CARE HOSPITAL OF RAHIM YAR KHAN (The Research of Medical Science Review, 2025)
Objectives: The study aimed to assess the frequency of common barriers faced by rural married women in adopting family planning methods during antenatal care visits at a tertiary care hospital in Rahim Yar Khan. Study Design: A cross-sectional study was conducted at Sheikh Zayed Medical College and Hospital, Rahim Yar Khan from January 24, 2025 to April 24, 2025 Methods: After ethical approval, 280 women aged 20-49 years were enrolled in the study. A structured questionnaire, consisting of closed-ended questions, was administered to gather data on socio-demographic characteristics and common barriers to family planning. Data were analyzed using IBM SPSS, version 27.0, with appropriate statistical tests, including chi-square and Fisher's exact tests, to assess the significance of the barriers. Results: Among the participants, 25% were aged 26-30 years, with the majority (60%) being illiterate or having education below matric. The most common barriers identified were husband reluctance (40% reluctant), illiteracy (40% illiterate), and affordability issues (45% with limited affordability). The odds of using family planning were lower among women with illiterate husbands (OR: 0.9, 95% CI: 0.6-1.4, p = 0.043), illiterate women (p < 0.0001), and women with lower household incomes (OR: 0.2, 95% CI: 0.1-0.6, p < 0.05). Religious beliefs were not a significant barrier (p = 0.112). Conclusion: The study concluded that socio-demographic factors and husband reluctance were the most prominent barriers to family planning adoption among rural married women. These findings highlight the need for targeted interventions to address these barriers.